Perspective of coaching football in women: japan women's challenge - Saski, N. (7th World Congress on Science and Football (WCSF), 2011, 2011)
On the `FIFA Ballon d'or 2010` (FIFA world award of Player and Coach of the Year)`, he was nominated for the Final 10 best coach for women football in the world. Mr Sasaki has been the head-coach of Japanese women soccer representative team and also Under 20 since 2007. After getting the place of the semi-finalist in 2008 Beijing game, his coaching was praised as `the world surprise was Japanese women team.` The lecture focuses about the essence and the strategy for reinforcement and development on football in women. One theme is the cooperation of defense and offense. Defense system must maintain to diminish the opuses strength by own quickness, cleverness and skillfulness. It needs long-term training from U20 to senior team. To get over the physical inferiority, the team must keep strengthen the adaptation power, the decision making in tough situation and improvement in the individual quality. Coach and players are walking together to be one team in consciousness and to make a strong `bond`. It is no good to push too much for the players altime. Coach should support the things which players make a goal by themselves. It is a time and a decision when the coach must lead strongly. Player`s motivation would raise with the ascertaining well. Main Achievement: 2007 World Cup China (Qualifying pool). AFCu19 (Finalist) 2008 Beijing Olympic Games (Semi-finalist) East-Asian Games (Champion) U20 World Cup Chile (Quarter- finalist) 2009 AFCu19 China Round (Champion) 2010 Chili-Cup (Champion) U20 World Cup Germany ..